Crafts And Professions Identified In Tibilis Through Archaeological Sources (Journal of Namibian Studies : History Politics Culture, 2024)
Historically, cities have emerged as epicenters for demographic convergence, epitomizing the nexus of authority and the crucibles for commercial and economic exchanges. They catalyze social transformations through intricate interactions and integrations, harnessing their organizational capacities and robust legal frameworks to meticulously orchestrate life. The domain of urban development has undergone a remarkable evolution and extensive expansion, positioning urban life as the quintessential manifestation of civilized existence. Within these urban confines, citizens are afforded a myriad of rights and luxuries, continually enhanced and diversified over time to facilitate individual and community well-being. This dynamic serves as a critical metric for evaluating the prosperity and welfare of urban centers. Tibilis, while maintaining a rustic and agrarian demeanor reminiscent of smaller hamlets, boasts 23 documented professions from antiquity, when wood was the primary resource, reflecting its untapped wealth.These professions, revealed through archaeological inscriptions, range from postal carriers (Viator) and livestock traders (Catervarius) to farmers (Arator) and landowners (Posse(ssor)). The city’s significant development has also fostered a flourishing of crafts such as pottery, construction, and carpentry, substantially contributing to its prosperity.